Redescription of Nogueirapis Moure, 1953 with two new species from the Amazon forest (Hymenoptera: Apidae: Meliponini) - Nogueira, David Silva; Feitosa Ribeiro, Cristiano; de Oliveira, Marcio Luiz (Zootaxa, 2020)
The bee genus Nogueirapis Moure is redescribed with the addition of new characters deriving from two new species from the Amazon rainforest. Nogueirapis batistai sp. nov. and N. rosariae sp. nov. are described and included in an identification key that covers all species of the genus. Occurrence records are updated for all species.